A survey on VoIP packet loss techniques. (1st January 2015) - Thirunavukkarasu, E.S.; Karthikeyan, E.
Voice over internet protocol (VoIP) is a group of hardware and software that facilitates people to utilise the internet as the transmission medium for telephone calls by transmitting voice data in packets using IP instead of using conventional circuit transmissions of the public switched telephone network (PSTN). VoIP is also considered as internet telephony, IP telephony or voice over the internet (VOI). VoIP communication practically needs a high-speed internet connection for consistent functionality. There are several internet telephony applications existing at present. VoIP has established necessities for data packets to arrive at their target in a more controlled time. The techniques are used to quantifying the survey of VoIP. The packet loss techniques are proposed to service the VoIP.